SYSTEMIC VASCULITIS: NOVELTY IN CLASSIFICATION, DIAGNOSIS, AND TREATMENT - N. A. Shostak; A. A. Klimenko (Klinicist, 2015)
Systemic vasculitides (SV) are a heterogeneous group of acute and chronic diseases, the most important pathomorphological sign of which is inflammation and necrosis of the vascular wall. The basis for the classification of SV is their etiology and pathogenesis, the type of affected vessels and the pattern of inflammation, predominant organ involvements, clinical manifestations, a genetic predisposition, and demographic characteristics. To diagnose vasculitis is a difficult task due to a broad spectrum of its clinical manifestations that depend on the predominant size of affected vessels, the involved organs and systems, and the magnitude of the inflammatory process. There are no specific laboratory tests for most forms of SV; nonspecific inflammatory measures and activated autoimmune reactions are noted to be higher. Screening for SV determines the levels of anti-neutrophil cytoplasmic antibodies (ANCA), cryoglobulins, anti-glomerular basement membrane antibodies, and anti-complement C1q antibodies. However, biopsy with its specimen being pathomorphologically characterized, as well as current noninvasive or minimally invasive diagnostic techniques remain relevant because of a large number of seronegative variants of vasculitis. The ANCA-associated vasculitis management algorithm developed by the British Society of Rheumatology has been presented in 2015. The timely diagnosis and treatment at the onset of SV is the basis for quality of life and survival improvement.